Menumbuhkan Minat Gemar Membaca Melalui Gerakan Literasi Bagi Siswa Sekolah Dasar - Sari Novrika Utami; Fajar Utama Ritonga (LP2M Universitas Muhammadiyah Enrekang, 2023)
Reading from an early age is considered unimportant and the influence of technology makes children's lack of interest in reading, therefore the importance of cultivating children's interest in reading in order to train children's thinking skills from an early age. Practice using group intervention methods in general began to intervene with students of SD Negeri 060831 Kota Medan, starting from the engagement stage to the termination stage. Some answers from students about things that make a lack of interest in reading are the influence of technology and lack of attention from parents in training students to be fluent in reading. From these answers, practitioners decided to create a literacy program whose activities could be carried out in the classroom and school library. From the program that has been run, it can be said to be successful because students already have a high interest and are trained to be fluent in reading